2023
DOI: 10.1158/2326-6066.cir-22-0483
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Podofilox as a Potent cGAMP–STING Signaling Enhancer with Antitumor Activity

Abstract: Cyclic GMP–AMP (cGAMP) is a second messenger that activates the stimulator of interferon genes (STING) innate immune pathway to induce the expression of type I interferons (IFNs) and other cytokines. Pharmacological activation of STING is considered a potent therapeutic strategy in cancer. In this study, we employed a cell-based phenotypic screen and identified podophyllotoxin (podofilox), a microtubule destabilizer, as a robust enhancer of the cGAMP–STING signaling pathway. We found that podofilox enhanced th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The exact mechanism of STING-mediated NF-kB signaling still need to be revealed, and further studies are required to investigate the mechanism for how MMAE and cGAMP regulates NF-kB signaling. In addition, MMAE showed synergistic effect with not only cGAMP, but also other STING agonists [ 26 ], suggesting that the combination of MMAE with other available STING agonists could also have antiviral activities, expanding possible therapeutic options. Collectively, these results support the notion that MMAE, a potent MDA with proven clinical safety at tested concentrations, might have potential to be used as antiviral drug in combination with STING agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism of STING-mediated NF-kB signaling still need to be revealed, and further studies are required to investigate the mechanism for how MMAE and cGAMP regulates NF-kB signaling. In addition, MMAE showed synergistic effect with not only cGAMP, but also other STING agonists [ 26 ], suggesting that the combination of MMAE with other available STING agonists could also have antiviral activities, expanding possible therapeutic options. Collectively, these results support the notion that MMAE, a potent MDA with proven clinical safety at tested concentrations, might have potential to be used as antiviral drug in combination with STING agonists.…”
Section: Discussionmentioning
confidence: 99%
“…So, disruption of the microtubule network not only seriously affects the viral replication cycle, such as viral entry, intracellular transport, and cell-to-cell spread [ 23 , 24 ], but also affects the proper distribution and function of organelles and vesicles, including the trafficking of STING [ 25 ]. Importantly, we found that a microtubule-destabilizing agent (MDA), podofilox, enhanced STING signaling with antitumor activity in our previous studies [ 26 ]. We were intrigued to hypothesize that MDAs may have antiviral activity by increasing STING signaling and innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulation between immunity and tumor progression contributes to the deterioration of cancer, with immunity and inflammation being closely intertwined. [96] The role of STING in tumors is multifaceted. Although current reports on STING agonists in tumor treatment are predominantly positive, the contrasting outcomes observed in preclinical and clinical trials highlight the challenges faced in overcoming tumors.…”
Section: Sting and Tumor Immunitymentioning
confidence: 99%
“…The tumor microenvironment (TME) is a highly intricate network. The dysregulation between immunity and tumor progression contributes to the deterioration of cancer, with immunity and inflammation being closely intertwined [96] . The role of STING in tumors is multifaceted.…”
Section: Biological Functions Of Stingmentioning
confidence: 99%
“…These discoveries offer insights into the potential connection between amyloid-like assemblies and the emergence of primitive protein enzymes during enzyme evolution. , Peptide sequences in reported artificial enzymes typically contain the following: (i) phenylalanine (F), which contributes π–π stacking interactions to form a hydrophobic core, fostering high levels of order for the self-assembly of short amyloid peptides and their derivatives. Additionally, the amyloid-like structure formed via the coordination of F molecules with zinc ions can serve as an artificial enzyme, exhibiting remarkable carbonic anhydrase–like activity . (ii) Histidine (H), frequently incorporated in the design of supramolecular catalysts and metal-free catalysis. , Notably, H can modulate the assembly behavior of peptides and induce enzyme-like catalysis to assemblies. (iii) Lysine (K), serving as a charged amino acid, provides hydrogen bonding and cation−π interactions and modulates the hydrophilic–hydrophobic balance of peptide molecules. It can be utilized to design peptide nanostructures with specific structures and functions. , The introduction of lysine into a system can expedite the catalytic activity of assemblies. These findings suggest the possibility of developing additional functional motifs to broaden the scope of peptide-based artificial enzymes.…”
Section: Introductionmentioning
confidence: 99%